Sosialisasi Pengaruh Bahaya Penyalahgunaan Narkoba Di Kalangan Siswa SMKN 1 Meureubo Aceh Barat - Arfriani Maifizar; Khairan; Sopar; Riki Yulianda (JPM: Jurnal Pengabdian Masyarakat, 2023)
The drug problem in West Aceh District, Aceh Province today is something that is urgent and complex. In the last decade the problem has become more widespread. Evidenced by the significant increase in the number of drug abusers or addicts. This research reveals that most drug users are teenagers or school-age students. Based on the results of field observations and interviews with the school. As for the condition/existing that SMKN 1 Meureubo as the implementing location still really needs cooperation with universities in the Meureubo sub-district to help socialize the dangers of drug abuse among students/youth. the results of observations identified that the problems that occurred at SMKN 1 Meureubo were as follows: Limited knowledge possessed by students regarding the benefits of socialization activities about the dangers of narcotics so far either given by teachers or the Department of Education and other related parties; Students and teachers do not yet/have specific material and skills that can discuss the effects of drug abuse for students at SMKN 1 Meureubo; There is a curiosity of teachers and students about participation in the activities of overcoming the dangers of narcotics in the West Aceh region; Having the same sense of responsibility between teachers, students and principals of SMKN 1 Meureubo to prevent the dangers of drug abuse from entering the world of education. The results of the dedication were the achievement of socialization at SMKN 1 Meureubo, with the implementation of several stages of socialization, namely: Formation of an activity team; Activity administration; Making outreach materials and training banners; Implementation of socialization; Evaluation of activities and activity reports.